Knowledge, Attitudes, and Practices in Relation to Reproductive Health Among Young Albanian Women - Zazo, Alketa; Kulluri, Eliona; Vrapi, Enxhi (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: National and international health policies focus on improving the sexual and reproductive health among women, therefore, understanding the factors that motivate or refrain women from accessing reproductive health services is central to those policies. This study aimed to document the level of sexual health-related knowledge, attitudes, and practices among women of reproductive age (24-49 years old) in Tirana, Albania. STUDY DESIGN: The main study instrument was a structured questionnaire focusing on knowledge, attitudes, and practices in relation to sexual and reproductive health. Quantitative data were collected through face-to-face interviews with 632 women of reproductive age in Tirana who were randomly selected to participate in the survey. Consent was taken and the data remained confidential. Data analysis was performed using SPSS version 14. RESULTS: Women, participating in this study, appeared to be well-informed regarding the risk factors associated with cervical cancer, yet only 32.7% had carried out a Pap-smear test. ‘Being healthy’, lack of diseases, lack of time, and for a minority of 9% the lack of knowledge were the main reasons listed for not undertaking cervical screening. More than half of the women report having good knowledge about sexually transmitted diseases-information that was mainly acquired through television (73.4%) and the internet (50.7%). The majority, 81.2%, of the women perceived themselves as not being at risk for sexually transmitted diseases and only 12% of women report to have gone to the health care center to ask for information or advice on sexually transmitted diseases prevention methods. A similar trend was witnessed regarding contraception. Most participants admitted to not using any mode of contraception or preferring the withdrawal method despite being informed of the main contraceptive options. Reasons for using or not the appropriate method were different. Major factors influencing decision-making on the contraception method were the male partner preferences and lack of knowledge about the role of the primary health care center as information and prescription provider for contraceptives. CONCLUSIONS: The findings do confirm the gap between knowledge and practices and suggest the need to develop and implement sexual and reproductive health services, which integrate adequately communication and health promotion strategies. Equally important is to continually monitor and collect data to better understand the population’s needs and where to focus the efforts to be able to deliver an improved, efficient, and satisfactory sexual health service.